Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Learning Cycle (LC) Berbantuan Media Wordwall di Kelas IV SDN 13 Kubu Gulai Bancah Kota Bukittinggi - Achmadi, Arya; Desyandri, Desyandri (Asian Journal of Early Childhood and Elementary Education, 2025)
This research is motivated by the less than optimal implementation of Pancasila Education learning carried out by teachers, so that it has an impact on the low learning outcomes of students in class IV SDN 13 Kubu Gulai Bancah Bukittinggi City. This study aims to describe the improvement of student learning outcomes in Pancasila Education learning by using the Learning Cycle (LC) model assisted by Wordwall Media in Class IV SDN 13 Kubu Gulai Bancah Kota Bukittinggi. This research is a class action research (PTK) that usses qualitative and quantitative approaches. It was carried out in two cycles, where cycle I consisted of two meetings and cycle II consisted of one meeting. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The subjects of this research were teachers and students of class IV SDN 13 Kubu Gulai Bancah Bukittinggi City. Data from the study were obtained from the teaching module assessment, implementation process, and learning outcomes. Data collection techniques using observation, tests and non-tests. The results showed an increase in: a) Teaching module cycle I with an average of 86.56% (Good) and cycle II 94.44% (Very Good), b) Teacher activities in the implementation of cycle I with an average of 81.93% (Good) and cycle II with an average of 91.66% (Very Good), while student activities in the implementation of cycle I with an average of 81.93% (Good), and cycle II 91.66% (Very Good), c) Assessment of student learning outcomes in cycle I obtained an average of 77.02 and cycle II obtained an average of 88.64. Based on these results it can be concluded that the Learning Cycle model assisted by Wordwall media can improve student learning outcomes in learning Pancasila Education in class IV SDN 13 Kubu Gulai Bancah Bukittinggi City.